EURAD state-of-the-art report on the understanding of radionuclide retention and transport in clay and crystalline rocks - Maes, Norbert; Churakov, Sergey; Glaus, Martin; Baeyens, Bart; Dähn, Rainer; Grangeon, Sylvain; Charlet, Laurent; Brandt, Felix; Poonoosamy, Jenna; Hoving, Alwina; Havlova, Vaclava; Fischer, Cornelius; et al. (Frontiers in Nuclear Engineering, 2024)
After isolation of radioactive waste in deep geological formations, radionuclides can enter to the biosphere by slow migration through engineered barriers and host rocks. The amount of radionuclides that migrate into the biosphere depends on the distance from the repository, dominant transport mechanism (diffusion vs advection), and the interaction of the dissolved radionuclides with minerals present in the host rock and engineered barrier systems. Within the framework of the European Union’s Horizon 2020 EURAD project (https://www.ejp-eurad.eu/), a series of state of the art reports have been drafted which form the basis of a series of papers. This state-of-the-art paper aims at providing a comprehensive overview of the current understanding of the underlying processes contributing to the radionuclide retention and migration in clay and crystalline host rocks in the European context for non-specialists. For each process, a brief theoretical background is provided together with current methodologies used to study these processes as well as references to key data. Thanks to the innovative research on retention and migration and the extensive knowledge collected for some decades (in the European context), the process understanding and insights are continuously improving, prompting to adapt and refine conceptual descriptions towards safety assessments. Nevertheless there remain important research questions to be investigated in the future which are enlisted at the end of the manuscript.